Solving nth-order Integro-differential Equations by Novel Generalized Hybrid Transform (European Journal of Pure and Applied Mathematics, 2023)
Recently, Shehu has introduced an integral transform called Shehu transform, which generalizes the two well-known integrals transforms, i.e. Laplace and Sumudu transform. In the literature, many integral transforms were used to compute the solution of integro-differential equations (IDEs). In this article, for the first time, we use Shehu transform for the computation of solution of $n^{\text{th}}$-order IDEs. We present a general scheme of solution for $n^{\text{th}}$-order IDEs. We give some examples with detailed solutions to show the appropriateness of the method. We present the accuracy, simplicity, and convergence of the proposed method through tables and graphs.
Keywords: Integrodifferential equations; Shehu transform; Integral transforms